A remarkable new species of Commelina (Commelinaceae) from western Mexico - Maldonado-Moreno, Claudia; Alvarez-Jiménez, Abel De Jesús; Juárez-Gutierrez, Héctor David; Alba, Guillermo Alatorre-De; Muñiz-Castro, Miguel Ángel (Phytotaxa, 2023)
Commelina occulta (Commelinaceae), a new endemic species from western Mexico, is described and illustrated. The new species is related to C. tuberosa complex and morphologically close to C. standleyi but differs in having broad leaf blades, larger, axillary inflorescences, glaucous spathaceous bracts with long peduncles, besides being more robust and glabrescent. According to IUCN criteria, the species was assessed as endangered (EN). A key to the western Mexico species of Commelina is provided.